Information Warfare, Threats and Information Security - D. N. Bespalov; M. A. Kazakov (Vestnik MGIMO-Universiteta)
The article presents the opposite, but dependent on each other's reality - Revolutionary War information,information security goals and objectives of their study within the scheme "challenge-response", methodological and analytical support, the role of elites and the information society in promoting information security. One of the features of contemporaneityis the global spread of ICT, combined with poor governance and other difficulties in the construction of innovation infrastructures that are based on them in some countries. This leads to the reproduction of threats, primarily related to the ability to use ICT for purposes that are inconsistent with the objectives of maintaining international peace and security, compliance with the principles of non-use of force, non-interference in the internal affairs of states, etc. In this regard, include such terms as "a threat of information warfare", "information terrorism" and so forth. Information warfare, which stay in the policy declared the struggle for existence, and relationships are defined in terms of "friend-enemy", "ours-foreign". Superiority over the opponent or "capture of its territory" is the aim of political activity. And information security, serving activities similar process of political control, including a set of components, is a technology until their humanitarian. From the context and the decision itself is the ratio of the achieved results of information and political influence to the target - a positive image of Russia. Bringing its policy in line with the demands of a healthy public opinion provides conductivity of theauthorities initiatives in the country and increases the legitimacy of the Russian Federation actions in the world.